2018
DOI: 10.1002/mawe.201700086
|View full text |Cite
|
Sign up to set email alerts
|

Influence of boron carbide content on the microstructure, tensile strength and fracture behavior of boron carbide reinforced aluminum metal matrix composites

Abstract: In the present work, an indigenously developed low cost modified stir casting technique is developed for the processing of 6061 Al‐B4C composites containing high‐volume fraction of boron carbide particles (up to 20 vol. %). The influence of varying reinforcement content on the spatial distribution of boron carbide in the aluminum matrix is qualitatively characterized using scanning electron microscope. At a lower volume fraction of reinforcement, wide particle free zone and large interparticle spacing were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…9 Some studies have been carried out on B 4 C doped materials, and it has been concluded that B 4 C particles improve thermal, 10 mechanical, 11,12 and physical properties. 13 While B 4 C particles doped metal matrix materials were frequently encountered, it was seen that there are limited studies on polymer matrix materials [14][15][16] in the literature. Kharat et al investigated the mechanical properties of boron carbide (B 4 C) and Tungsten disulphide (WS 2 ) doped epoxy composites in a study.…”
Section: Introductionmentioning
confidence: 99%
“…9 Some studies have been carried out on B 4 C doped materials, and it has been concluded that B 4 C particles improve thermal, 10 mechanical, 11,12 and physical properties. 13 While B 4 C particles doped metal matrix materials were frequently encountered, it was seen that there are limited studies on polymer matrix materials [14][15][16] in the literature. Kharat et al investigated the mechanical properties of boron carbide (B 4 C) and Tungsten disulphide (WS 2 ) doped epoxy composites in a study.…”
Section: Introductionmentioning
confidence: 99%
“…The main task of the basket is to maintain subcriticality of the fuel assembly by means of thermal neutron absorption [1][2][3]. Neutron absorption is facilitated by isotope 10 B with a large neutron absorption cross section (3850 barn at 25.3 meV). Isotope 10 B also has relevant natural abundance (19.8%) which makes it attractive for large-scale use [1].…”
Section: Introductionmentioning
confidence: 99%
“…The production of MMCs using stir casting might lead to non-uniform particle distribution. Porosity [8], interfacial reactions [9] or poor wetting between aluminium and boron carbide [10] can have a negative impact on the performance of the final product. Sintering techniques such as hot pressing do also have some porosity [11], but they can be utilized to produce MMCs with more homogeneous particle distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Though these are light-weight metals they do not meet the demand towards their material properties such as mechanical and tribological. A new kind of material called nanocomposite material was developed in which stiff ceramic particle are incorporated to get a notable improvement in properties [1][2][3][4] but low ductility and poor toughness limit the use of these materials, these being a result of poor wettability, low ductility, porosity, and clustering due to micronano particle sizes in nature. [5] Hence, several methods were introduced to minimize these defects.…”
Section: Introductionmentioning
confidence: 99%